Battery monomer and preparation method thereof, battery device and power utilization device

By using carbon nanotubes with long and average tube lengths to wrap and bind the negative electrode active material in the negative electrode film layer, the problem of degradation of cycle stability caused by expansion of the negative electrode sheet of the battery is solved, and higher cycle stability is achieved.

CN119812436APending Publication Date: 2025-04-11CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510005634.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the charging and discharging cycle of the battery, the negative electrode plate is prone to expand, resulting in a decrease in the cycle stability of the battery.

Method used

Carbon nanotubes are added to the negative electrode film layer, and the average tube length of the carbon nanotubes is greater than or equal to 40 μm. By wrapping and binding the negative electrode active material, the cohesion force is improved and the degree of expansion is reduced.

Benefits of technology

It effectively suppresses the expansion of the negative electrode sheet and improves the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812436A_ABST
    Figure CN119812436A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a battery monomer, a preparation method thereof, a battery device and a power utilization device. The battery monomer comprises a negative pole piece, the negative pole piece comprises a negative pole film layer, the negative pole film layer comprises a negative pole active material and a carbon nano tube, the carbon nano tube is attached to the surface of the negative pole active material, the average tube length of the carbon nano tube is greater than or equal to 40 microns, and the negative pole active material comprises graphite. According to the design mode provided by the invention, the cycle stability of the battery is improved by reducing the expansion degree of the negative pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a battery cell and a preparation method thereof, a battery device and an electrical device. Background Art

[0002] With the development of new energy technology, batteries are used more and more widely, such as in mobile phones, laptops, battery cars, electric cars, energy storage devices, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. This places higher and higher requirements on battery performance. Summary of the invention

[0003] In view of the above problems, the present application provides a battery cell and a method for preparing the same, a battery device and an electrical device, which improve the cycle stability of the battery by reducing the expansion degree of the negative electrode plate.

[0004] In a first aspect, the present application provides a battery cell, the battery cell comprising a positive electrode sheet and a negative electrode sheet;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer located on at least one side surface of the negative electrode current collector;

[0006] The negative electrode film layer comprises a negative electrode active material and carbon nanotubes, and the average tube length of the carbon nanotubes is greater than or equal to 40 μm;

[0007] The negative electrode active material includes graphite.

[0008] In some embodiments, the average tube length of the carbon nanotubes is 60 μm to 500 μm.

[0009] In some embodiments, the average diameter of the carbon nanotubes is 0.8 nm to 20 nm.

[0010] In some embodiments, the tensile strength of the carbon nanotubes is 30 Gpa to 55 Gpa;

[0011] The elastic modulus of the carbon nanotubes is 0.5TPa to 0.9TPa.

[0012] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes, and the mass percentage content of the single-walled carbon nanotubes in the negative electrode film layer is C1, 0.3%≤C1≤1.5%;

[0013] The average diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm.

[0014] In some embodiments, the carbon nanotubes include multi-walled carbon nanotubes, and the mass percentage content of the multi-walled carbon nanotubes in the negative electrode film layer is C2, 0.5%≤C2≤1.5%;

[0015] The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm.

[0016] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0017] The average diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm.

[0018] The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm;

[0019] The mass percentage content of the single-walled carbon nanotube in the negative electrode film layer is C1, and the mass percentage content of the multi-walled carbon nanotube in the negative electrode film layer is C2, satisfying: (C2×3 / 5+C1)≥0.3%;

[0020] 0.3%≤C1≤1.5%; 0.5%≤C2≤1.5%.

[0021] In some embodiments, the compaction density of the negative electrode film is 1.55 g / cm 3 ~1.65g / cm 3 ;

[0022] The bonding force between the negative electrode film layer and the negative electrode current collector is 7N / m to 20N / m;

[0023] The cohesive force of the negative electrode film layer is 50 N / m to 200 N / m.

[0024] In some embodiments, the negative electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.

[0025] In some embodiments, the negative electrode film layer further comprises any one or more of carbon black and graphene.

[0026] In some embodiments, the specific surface area of ​​the carbon black is ≥100 m 2 / g;

[0027] and / or;

[0028] The number of layers of the graphene is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm;

[0029] In some embodiments, the mass percentage of the carbon black and / or graphene in the positive electrode film layer is greater than zero and less than or equal to 2.5%.

[0030] In some embodiments, the negative electrode film layer includes a binder;

[0031] The above-mentioned adhesive includes acryl-based copolymer;

[0032] The acryl-based copolymer includes any one or more of a structural unit derived from an acrylic acid monomer, a structural unit derived from an acrylamide monomer, a structural unit derived from an acrylonitrile monomer, and a structural unit derived from an acrylate monomer.

[0033] In some embodiments, the mass percentage content of the acryl-based copolymer in the negative electrode film layer is 1% to 3%.

[0034] In some embodiments, the median particle size of the graphite is Dv50, which is 8 μm to 20 μm.

[0035] In some embodiments, the graphite comprises a porous structure, and the pore volume of the graphite is 1.0 cm 3 / g~3.0cm 3 / g.

[0036] In some embodiments, the oil absorption value of the graphite is 45 cm 3 / 100g~65cm 3 / 100g.

[0037] The second aspect of the present application is to provide a method for preparing the battery monomer according to the first aspect, comprising the following process:

[0038] Providing a carbon nanotube dispersion comprising carbon nanotubes, a first dispersant and a first solvent;

[0039] Preparing negative electrode slurry: dispersing the negative electrode active material, the carbon nanotube dispersion and the second dispersant in the second solvent, and mixing them to form negative electrode slurry;

[0040] Preparing a negative electrode sheet: coating a negative electrode slurry on at least one side of a negative electrode current collector to form a negative electrode film layer;

[0041] Prepare battery cells: Assemble the negative electrode sheet, positive electrode sheet and separator together.

[0042] In some embodiments, the first dispersant includes sodium carboxymethyl cellulose, and the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.7 and less than 1.0;

[0043] The second dispersant includes sodium carboxymethyl cellulose, and the substitution degree of the sodium carboxymethyl cellulose is 1.0-1.2.

[0044] In some embodiments, in the carbon nanotube dispersion, the mass ratio between the carbon nanotubes and the first dispersant is 100:(50-250);

[0045] and / or;

[0046] The solid content of the carbon nanotube dispersion is 0.6% to 1.5%.

[0047] In some embodiments, the carbon nanotube dispersion further comprises a surfactant;

[0048] The mass percentage content of the above surfactant is 2% to 5%;

[0049] The above-mentioned surfactant includes any one or more of glutamic acid surfactant and glycine surfactant.

[0050] A third aspect of the present application is to provide a battery device, which includes the battery cell described in the first aspect or the battery cell manufactured by the preparation method described in the second aspect.

[0051] A fourth aspect of the present application is to provide an electrical device, which includes the battery device described in the third aspect.

[0052] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Also, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0054] Figure 1 A schematic diagram of the battery structure of some embodiments of the present application;

[0055] Figure 2 This is a schematic diagram of the exploded structure of batteries in some embodiments of the present application;

[0056] Figure 3 A schematic diagram of a vehicle structure of some embodiments of the present application;

[0057] Figure 4 A schematic diagram of the structure of a battery pack according to some embodiments of the present application;

[0058] Figure 5 A schematic diagram of the structure of a secondary battery in some embodiments of the present application;

[0059] Figure 6 A schematic diagram of the structure of a negative electrode sheet of some embodiments of the present application;

[0060] Figure 7Another schematic diagram of the structure of the negative electrode sheet of some embodiments of the present application;

[0061] Figure 8 This is a scanning electron microscope image of the negative electrode sheet of some embodiments of the present application.

[0062] The reference numerals in the specific implementation manner are as follows:

[0063] 10000, vehicles;

[0064] 1000, battery; 2000, controller; 3000, motor;

[0065] 100. Battery cell;

[0066] 200, box body; 210, first part; 220, second part;

[0067] 10. Secondary battery;

[0068] 101, housing; 102, electrode assembly; 103, cover plate;

[0069] 1. Negative electrode sheet; 11. Negative electrode current collector; 12. Negative electrode film layer;

[0070] 12b, first surface; 12a, second surface; 12a', third surface;

[0071] 2. Positive electrode;

[0072] 3. Isolation parts;

[0073] Coordinate axis x direction: the stacking direction or thickness direction of the pole piece;

[0074] Coordinate axis y direction: length direction or width direction of the pole piece. DETAILED DESCRIPTION

[0075] Hereinafter, the battery cell and its preparation method, battery device and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0076] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0077] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0078] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0079] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0080] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0081] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0082] If not otherwise specified, in this application, the terms "first", "second", etc. are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary and secondary relationship of the indicated technical features.

[0083] Unless otherwise specified, in this application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple sheets" refers to more than two sheets (including two sheets).

[0084] Unless otherwise specified, the orientations or positional relationships indicated by technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.

[0085] Batteries have been widely used in various products due to their advantages such as high energy density, long cycle life, safety and reliability. In recent years, as the demand for batteries as energy has increased significantly, higher requirements have been placed on battery performance such as cycle stability.

[0086] During the charge and discharge cycle of the battery, some irreversible reactions will occur while the positive and negative active materials are being released and embedded. The products of these reactions are deposited on the surface of the electrode as insoluble by-products, which can easily cause irreversible expansion of the battery, resulting in an increase in the expansion coefficient of the electrode, and further causing the electrolyte in some areas of the battery cell body to be squeezed out, forming some "dry areas" inside the battery cell body. The existence of "dry areas" leads to a reduction in the active substances that can participate in the charge and discharge reactions, causing uneven local state of charge (SOC) in the battery, accelerated local aging in the battery, and a decline in the battery's cycle performance, which ultimately affects the battery life.

[0087] Based on the above considerations, in order to reduce the expansion degree of the negative electrode plate to improve the cycle stability of the battery, the present application provides a battery cell and a preparation method thereof, a battery device and an electrical device.

[0088] First, the present application discloses a battery cell, which includes a positive electrode plate, an isolation member and a negative electrode plate; the negative electrode plate includes a negative electrode collector and a negative electrode film layer located on at least one side of the negative electrode collector; the negative electrode film layer includes a negative electrode active material and carbon nanotubes, and the average tube length of the carbon nanotubes is greater than or equal to 40μm; the negative electrode active material includes graphite.

[0089] In the battery cell provided by the present application, carbon nanotubes are added to the negative electrode active material, and the carbon nanotubes are attached to the surface of the negative electrode active material, wherein the average tube length of the carbon nanotubes is greater than or equal to 40 μm, and the carbon nanotubes of the average tube length have a linear structure, which is convenient for attachment and winding on the surface of the negative electrode active material. In addition, the mechanical properties of the carbon nanotubes of the average tube length are also good, such as good tensile strength and elastic modulus. When the volume of the active material expands during the battery charging and discharging process, the carbon nanotubes entangle and bind the negative electrode active material, which increases the cohesive force between the negative electrode active materials and reduces the expansion of the active materials, so the expansion of the negative electrode sheet is finally suppressed to a certain extent, thereby improving the cycle stability of the battery.

[0090] Battery Cell

[0091] In the embodiment of the present application, the battery cell may be a secondary battery. A secondary battery refers to a battery cell that can be continuously used by activating active materials by charging after the battery cell is discharged.

[0092] The battery cell can be a lithium ion battery, a sodium ion battery, a sodium lithium ion battery, a lithium metal battery, a sodium metal battery, a lithium sulfur battery, a magnesium ion battery, a nickel hydrogen battery, a nickel cadmium battery, a lead storage battery, etc., which is not limited in the embodiments of the present application.

[0093] Electrode assembly

[0094] A battery cell generally includes an electrode assembly. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, which is arranged between the negative electrode sheet and the positive electrode sheet. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which can prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through.

[0095] Battery device

[0096] The battery apparatus mentioned in the embodiments of the present application may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells, which are connected in series, in parallel or in mixed connection through a busbar component.

[0097] In some embodiments, a battery cell assembly is generally formed by arranging a plurality of battery cells.

[0098] As an example, the battery cell assembly may be a battery module, which is formed by arranging and fixing a plurality of battery cells to form an independent module. As an example, the battery module may be formed by bundling a plurality of battery cells by a cable tie.

[0099] In some embodiments, the battery device may be a battery pack, which includes a case and one or more battery cell assemblies, wherein the battery cell assemblies are accommodated in the case.

[0100] As an example, the battery cell assembly may be a battery module, and the battery cell assembly may be accommodated in the box by fixing the battery module in the box.

[0101] As an example, the battery cell assembly may also be housed in the case by directly fixing a plurality of battery cells to the case.

[0102] As an example, the box may include a first box and a second box. The first box and the second box are buckled together to form a closed space inside the box to accommodate the battery cell assembly. The closed here means covered or closed, which can be sealed or unsealed. The first box can be a top cover or a bottom plate.

[0103] As an example, the box body may include a top cover, a frame and a bottom plate. The top cover and the bottom plate are respectively connected to the frame, so that a closed space is formed inside the box body to accommodate the battery cell assembly.

[0104] In some embodiments, the box body can be used as a part of the chassis structure of the vehicle. For example, part of the box body can become at least a part of the floor of the vehicle, or part of the box body can become at least a part of the cross beam and longitudinal beam of the vehicle.

[0105] The battery cell of the present application may include an outer packaging. The outer packaging may be used to encapsulate the electrode assembly and electrolyte composed of the above-mentioned battery cell. The outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and the plastic includes but is not limited to polypropylene, polybutylene terephthalate, and polybutylene succinate, etc.

[0106] The present application has no particular limitation on the shape of the battery, which may be cylindrical, square or any other shape. For example, Figure 1 The secondary battery 10 is a square structure as an example.

[0107] According to some embodiments of the present application, Figure 2 , the outer packaging may include a shell 101 and a cover plate 103. Among them, the shell 101 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 101 has an opening connected to the receiving cavity, and the cover plate 103 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 102 through a winding process or a lamination process. The electrode assembly 102 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 102. The number of electrode assemblies 102 contained in the secondary battery 10 can be one or more, and those skilled in the art can select according to specific actual needs.

[0108] The electrode assembly 102 provided in the present application is applied to a battery cell, which is beneficial to improving the performance of the battery cell. The battery cell can be used as a power source for an electrical device or as an energy storage unit for an electrical device. The electrical device is applied to the power field, such as mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but not limited to the above-mentioned fields.

[0109] For the convenience of explanation, some embodiments of the present application are described by taking a vehicle as an example of an electrical device.

[0110] Please refer to Figure 3 , Figure 3A schematic diagram of the structure of a vehicle 10000 provided for some embodiments of the present application. The vehicle 10000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 1000 is provided inside the vehicle 10000, and the battery 1000 may be provided at the bottom, head or tail of the vehicle 10000. The battery 1000 may be used to power the vehicle 10000, for example, the battery 1000 may be used as an operating power source for the vehicle 10000. The vehicle 10000 may also include a controller 2000 and a motor 3000, and the controller 2000 is used to control the battery 1000 to power the motor 3000, for example, for the starting, navigation and working power requirements of the vehicle 10000 during driving.

[0111] In some embodiments of the present application, the battery 1000 can not only serve as the operating power source of the vehicle 10000, but also serve as the driving power source of the vehicle 10000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 10000.

[0112] Please refer to Figure 4 , Figure 4 An exploded view of a battery 1000 provided in some embodiments of the present application. The battery 1000 includes a housing 200 and a battery cell 100. Conventional battery cells include primary batteries or secondary batteries. The present application specifically protects secondary batteries 10. The battery cell 100 is accommodated in the housing 200. The housing 200 is used to provide a storage space for the battery cell 100. The housing 200 can adopt a variety of structures.

[0113] In some embodiments, the box 200 may include a first portion 210 and a second portion 220, the first portion 210 and the second portion 220 cover each other, and the first portion 210 and the second portion 220 jointly define a storage space for accommodating the battery cell 100. The second portion 220 may be a hollow structure with one end open, and the first portion 210 may be a plate-like structure, and the first portion 210 covers the open side of the second portion 220, so that the first portion 210 and the second portion 220 jointly define a storage space; the first portion 210 and the second portion 220 may also be hollow structures with one side open, and the open side of the first portion 210 covers the open side of the second portion 220. Of course, the box 200 formed by the first portion 210 and the second portion 220 may be in various shapes, such as a cylinder, a cuboid, etc.

[0114] In the battery 1000, there may be multiple battery cells 100, and the multiple battery cells 100 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 100 are both connected in series and in parallel. The multiple battery cells 100 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 100 is accommodated in the box 200; of course, the battery 1000 may also be a battery 1000 module formed by connecting multiple battery cells 100 in series, in parallel, or in a mixed connection, and then the multiple battery 1000 modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 200. The battery 1000 may also include other structures, for example, the battery 1000 may also include a converging component for realizing electrical connection between the multiple battery cells 100.

[0115] Battery Cell

[0116] In some embodiments, the present application discloses a battery cell, which includes a positive electrode plate, an isolation member and a negative electrode plate; the negative electrode plate includes a negative electrode collector and a negative electrode film layer located on at least one side of the negative electrode collector; the negative electrode film layer includes a negative electrode active material and carbon nanotubes, and the average tube length of the carbon nanotubes is greater than or equal to 40μm; the negative electrode active material includes graphite.

[0117] The battery cell of the present application includes a positive electrode sheet, a separator and a negative electrode sheet, wherein each component can be wound or laminated to form a battery cell. Figure 5 The secondary battery 10 formed by a lamination method is shown in FIG. Figure 5 It can be seen that a negative electrode sheet 1 or a positive electrode sheet 2 is placed between two adjacent separators 3, and the negative electrode sheets 1 and the positive electrode sheets 2 are alternately arranged in sequence along the stacking direction (coordinate axis x direction). The number and size of the negative electrode sheets 1 and / or the positive electrode sheets 2 can be selected according to actual conditions, and this application will not be repeated. Figure 5 Only one lamination method is illustrated in the figure, and other lamination or winding methods are within the protection scope of this application.

[0118] like Figure 6 As shown in the figure, the negative electrode sheet 1 includes a negative electrode current collector 11 and a negative electrode film layer 12 located on at least one side of the negative electrode current collector 11, wherein: Figure 6 It is schematically shown that the negative electrode film layer 12 is disposed on any side surface of the negative electrode current collector 11, and the negative electrode film layer 12 can also be disposed on both side surfaces of the negative electrode current collector 11. The negative electrode film layer 12 is formed on the surface of the negative electrode current collector 11 by any conventional method in the art, such as coating, deposition, etc.

[0119] The carbon nanotubes in this application refer to carbon allotropes, which are hollow tube structures with a diameter of up to several hundred nanometers formed by curling a single or multi-layer graphene sheet at a certain spiral angle, and the tube wall of the hollow tube structure includes one or more cylindrical layers of carbon atoms. The microstructure of the carbon nanotubes gives it a one-dimensional quantum effect, so the carbon nanotubes have good tensile strength and elastic modulus.

[0120] The carbon nanotubes of the present application include any one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0121] The single-walled carbon nanotube of the present application refers to a single cylindrical layer of carbon atoms, and the multi-walled carbon nanotube of the present application refers to two or more layers of carbon atoms connected by intermolecular forces, or a single layer of carbon atoms wound several times around a cylindrical hollow core.

[0122] There are intermolecular forces between the negative electrode active material and the carbon nanotubes of the present application. The intermolecular forces refer to the mutual forces between molecules. Although these forces are weaker than the strength of the chemical bonds within the molecules, they play a key role in the physical properties of the material. For example, van der Waals forces, etc. On the one hand, this force facilitates the attachment of carbon nanotubes to the surface of the negative electrode active material, and on the other hand, it weakens the forces between adjacent carbon nanotubes to increase the uniformity of the dispersion of carbon nanotubes in the negative electrode active material.

[0123] In the present application, the average tube length of the carbon nanotubes is greater than or equal to 40 μm. On the one hand, the carbon nanotubes with this average tube length have a linear structure, which is convenient for attachment and winding around the surface of the negative electrode active material. On the other hand, the carbon nanotubes with this average tube length also have certain mechanical properties, such as good tensile strength and elastic modulus. When the active material expands in volume during the battery charging and discharging process, the carbon nanotubes entangle and bind the negative electrode active material, thereby improving the cohesive force between the negative electrode active materials and reducing the expansion degree of the active material.

[0124] The carbon nanotubes of the present application have a one-dimensional tubular structure, which includes a structure in two dimensions, wherein the diameter of the one-dimensional tubular structure is nanometer-level. The length of the one-dimensional tubular structure refers to the distance between one end and the other end of the tubular structure. The length of the one-dimensional tubular structure can be measured by any method commonly used in the art, such as by photographing the carbon nanotubes using a scanning electron microscope or a scanning transmission electron microscope.

[0125] The present application discloses a method for determining the average tube length of carbon nanotubes in a negative electrode film layer in some embodiments. The specific process is as follows: the present application first places a battery cell in a 1.0 mol / L sodium hydroxide aqueous solution at room temperature for discharge treatment. After the discharge is completed, the negative electrode sheet is manually disassembled to obtain the negative electrode sheet. A cryo-focused ion beam (FIB) is used to finely slice the negative electrode sheet layer by layer at different thickness positions (the smallest scale can reach nanometer-level thin slices), and separates different layers of samples at different thickness positions;

[0126] Place the samples of different layers at different positions in a scanning electron microscope, adjust the magnification of the equipment to 30K / 40K, select 20 to 50 carbon nanotubes in the field of view, and perform length statistics. The average length is the average length of the carbon nanotubes (um).

[0127] The graphite of the present application is an allotrope of carbon, including artificial graphite and natural graphite. The preparation method of artificial graphite in the present application comprises: providing raw materials, performing crushing and shaping → granulation → graphitization treatment → performing surface roughening treatment to obtain artificial graphite materials. The raw materials in these embodiments of the present application can be one or more of raw coke, calcined coke, and calcined petroleum coke; further, the raw materials include one or more of needle-shaped raw petroleum coke, non-needle-shaped raw petroleum coke, needle-shaped coal-based raw coke, non-needle-shaped coal-based raw coke, calcined needle coke, and calcined petroleum coke. The crushing of the present application can be carried out by devices and methods known in the art, such as air flow crushers, mechanical crushers, or roller mills. A large number of too small particles are usually produced during the crushing process, and sometimes too large particles are also produced. Therefore, after crushing, classification can be performed as needed to remove too small particles and too large particles in the crushed powder. After classification, a particle product with a good particle size distribution can be obtained, which is conducive to subsequent molding and / or granulation processes. Classification can be performed by devices and methods known in the art, such as a grading screen, a gravity classifier, or a centrifugal classifier. The shaping of the present application can be formed by equipment (such as a molding machine or other molding equipment) and methods known in the art. For example, the edges and corners of the obtained granular product are polished to facilitate subsequent operations and make the obtained product have higher stability. The granulation of the present application includes granulation using a device known in the art such as a granulator. The granulator generally includes a stirred reactor and a temperature control module for the reactor. In addition, the volume median particle size of the obtained product can be controlled by adjusting the process conditions such as stirring speed, heating rate, granulation temperature and cooling rate during the granulation process. The graphitization treatment of the present application includes high-temperature graphitization treatment and low-temperature graphitization treatment. In some embodiments, any one or two of the high-temperature graphitization treatment and the low-temperature graphitization treatment can be appropriately selected for treatment according to actual specific needs. Alternatively, the high-temperature graphitization treatment and / or the low-temperature graphitization treatment can be repeated. The surface roughening treatment of the present application includes the conventional treatment method in the art, such as physical methods.

[0128] The graphite of the present application includes any one of micro-expanded graphite or expanded graphite. Micro-expanded graphite refers to graphite with a loose volume change (i.e., expansion multiple) of 80 to 200 before and after expansion, and expanded graphite refers to graphite with a loose volume change (i.e., expansion multiple) of >200 before and after expansion. The micro-expanded graphite and / or expanded graphite of the present application are used as negative electrode active materials before and after battery recycling. Although the graphite itself has a certain expansion and is not conducive to the stability of the cycle, the carbon nanotubes provided by the present application are used to wrap and bind the graphite, thereby increasing the cohesive force of the graphite and reducing the expansion of the negative electrode sheet. In some embodiments of the present application, the expansion starting temperature of the micro-expanded graphite or expanded graphite is selected to be 75±5°C.

[0129] The graphite of the present application is suitable for high-rate fast-charging batteries, such as 3C, 4C, 5C, 6C and other charging windows. When used at such high rates, the negative electrode will obviously swell. The carbon nanotubes designed in the present application are attached and entangled on the graphite surface and exert certain constraints on the graphite, which is beneficial to reduce the degree of expansion of the negative electrode, thereby reducing the expansion of the negative electrode plate.

[0130] In some embodiments, the average tube length of the carbon nanotubes is 60 μm to 500 μm.

[0131] The definition and determination method of the average tube length of carbon nanotubes in this application remain the same as above, and will not be further elaborated in this application.

[0132] Generally, the longer the carbon nanotubes of the present application are, the easier it is to attach to, entangle with, and bind the negative electrode active materials, thereby further improving the cohesive force between the negative electrode active materials.

[0133] In these embodiments, the present application discloses that the average tube length of the carbon nanotubes is any one of 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 110μm, 150μm, 200μm, 210μm, 250μm, 300μm, 310μm, 350μm, 400μm, 410μm, 450μm, 500μm or any one of the values ​​satisfying the above two ranges.

[0134] In some embodiments, the average diameter of the carbon nanotubes is 0.8 nm to 20 nm.

[0135] The diameter of the carbon nanotube in this application refers to the outer diameter of the carbon nanotube. As mentioned above, the carbon nanotube refers to a hollow tube structure with a diameter of at most several hundred nanometers formed by curling a single layer or multiple layers of graphene sheets according to a certain spiral angle. The measurement method of the diameter of the carbon nanotube includes any conventional method in the art, and can be measured by a similar measurement method when measuring the length of the carbon nanotube. As mentioned above, after using a cryo-focused ion beam (FIB) to obtain different layers of samples at different thickness positions of the negative electrode, the different layers of samples at different positions are placed in a projection electron microscope, the magnification of the equipment is adjusted to 100K, 20 to 50 carbon nanotubes are selected in the field of view, and the diameter is counted. The average value of the diameter is the average value (nm) of the carbon nanotube diameter.

[0136] The average diameter of the carbon nanotubes in the present application meets the above range, which facilitates the carbon nanotubes to adhere to and wrap around the surface of the negative electrode active material and further enhances the binding of the negative electrode active material.

[0137] In these embodiments, the present application discloses that the average tube diameter of the above-mentioned carbon nanotubes is any one of 0.8nm, 0.9nm, 1.0nm, 2.0nm, 3.0nm, 4.0nm, 5.0nm, 6.0nm, 7.0nm, 8.0nm, 9.0nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, and 20nm, or any one of the values ​​satisfying the above two ranges.

[0138] In some embodiments, the tensile strength of the carbon nanotubes is 30 Gpa to 55 Gpa;

[0139] The elastic modulus of the carbon nanotubes is 0.5TPa to 0.9TPa.

[0140] The tensile strength of the present application refers to the critical value of the material's transition from uniform plastic deformation to local concentrated plastic deformation, and is used to characterize the material's resistance to maximum uniform plastic deformation. Before the tensile specimen is subjected to the maximum tensile stress, the deformation is uniform and consistent, but after exceeding the maximum tensile stress, the carbon nanotubes begin to neck, i.e., concentrated deformation occurs.

[0141] The elastic modulus of the present application refers to the material in the elastic deformation stage, the corresponding stress and strain are in direct proportion (ie, in accordance with Hooke's law), and its proportionality coefficient is called the elastic modulus. The elastic modulus also refers to Young's modulus.

[0142] The method for measuring the tensile strength and elastic modulus of the carbon nanotubes in the present application includes any conventional measurement method in the art, wherein the tensile strength can be measured by atomic force microscopy and with reference to GB / T2651-2023. The elastic modulus can also be measured by atomic force microscopy and tensile test, and the specific tensile test can refer to GB / T2651-2023.

[0143] The elastic modulus and tensile strength of the carbon nanotubes described in the present application mainly refer to the mechanical properties of the carbon nanotubes as raw materials in the process of preparing the electrode. Since the mechanical properties of the carbon nanotubes hardly change during the charging and discharging process of the battery, the present application also believes that in the battery cell, the elastic modulus and tensile strength of the carbon nanotubes satisfy the above numerical range.

[0144] The carbon nanotubes of the present application not only meet the above average tube length and average tube diameter, but also have certain tensile strength and elastic modulus, so as to better bind the negative electrode active material.

[0145] In these embodiments, the present application discloses that the tensile strength of the carbon nanotubes is any one of 30 Gpa, 31 Gpa, 32 Gpa, 33 Gpa, 34 Gpa, 35 Gpa, 36 Gpa, 37 Gpa, 38 Gpa, 39 Gpa, 40 Gpa, 41 Gpa, 42 Gpa, 43 Gpa, 44 Gpa, 45 Gpa, 46 Gpa, 47 Gpa, 48 Gpa, 49 Gpa, 50 Gpa, 51 Gpa, 52 Gpa, 53 Gpa, 54 Gpa, and 55 Gpa, or any one of the values ​​satisfying the above two ranges.

[0146] The present application discloses in these embodiments that the elastic modulus of the carbon nanotubes is any one of 0.5TPa, 0.6TPa, 0.7TPa, 0.8TPa, 0.9TPa or any one of the values ​​falling within the above two ranges.

[0147] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes, and based on the mass of the negative electrode film layer, the mass percentage content of the single-walled carbon nanotubes is C1, 0.3%≤C1≤1.5%;

[0148] The average diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm.

[0149] The present application selects to add single-walled carbon nanotubes in the negative electrode film layer because the diameter of the single-walled carbon nanotubes is relatively smaller, which is convenient for better binding and winding of the negative electrode active material. The present application further controls the mass percentage content of the single-walled carbon nanotubes in the negative electrode film layer, which is conducive to further increasing the binding effect, and also controls the influence of the carbon nanotubes on other components in the negative electrode film layer.

[0150] In these embodiments, the present application discloses that the mass percentage content of single-walled carbon nanotubes in the negative electrode film layer is C1 is any one of 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any one of the above two ranges.

[0151] In some embodiments, the carbon nanotubes include multi-walled carbon nanotubes, and based on the mass of the negative electrode film layer, the mass percentage content of the multi-walled carbon nanotubes is C2, 0.5%≤C2≤1.5%;

[0152] The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm.

[0153] Although the single-walled carbon nanotubes of the present application have better binding properties than multi-walled carbon nanotubes, they are prone to agglomeration. In addition, in the preparation of the negative electrode film layer containing carbon nanotubes, single-walled carbon nanotubes are not easy to disperse. Agglomeration will affect the binding properties of carbon nanotubes to the negative electrode active material to a certain extent. Therefore, the present application can also choose to use multi-walled carbon nanotubes and control the amount of multi-walled carbon nanotubes in the negative electrode active material.

[0154] In these embodiments, the present application discloses that the mass percentage content of multi-walled carbon nanotubes in the negative electrode film layer is C2, which is any one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any one of the values ​​satisfying the above two ranges.

[0155] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0156] The average diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm.

[0157] The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm;

[0158] Based on the mass of the negative electrode film layer, the mass percentage content of the single-walled carbon nanotube is C1, and the mass percentage content of the multi-walled carbon nanotube is C2, satisfying: (C2×3 / 5+C1)≥0.3%;

[0159] 0.3%≤C1≤1.5%; 0.5%≤C2≤1.5%.

[0160] As mentioned above, single-walled carbon nanotubes have better binding properties on negative electrode active materials than multi-walled carbon nanotubes, while multi-walled carbon nanotubes are less likely to agglomerate than single-walled carbon nanotubes. Therefore, in some embodiments, the present application discloses that the negative electrode film layer contains both single-walled carbon nanotubes and multi-walled carbon nanotubes. At the same time, experimental research has found that 3 parts by mass of multi-walled carbon nanotubes can play the same binding function on negative electrode active materials as 1 part by mass of single-walled carbon nanotubes. Therefore, when selecting the two for use in combination, the present application controls the relationship between the amounts of the two to better exert the binding properties of carbon nanotubes on negative electrode active materials.

[0161] In some embodiments, when the above-mentioned battery cell is in the initial state, the thickness of the negative electrode film layer is h1; the initial state here refers to the battery cell after assembly and before use, and may also refer to the thickness after cold pressing during the preparation of the negative electrode plate. Since the thickness of the negative electrode film layer changes to a limited extent before being assembled into a battery cell and before use, this application ignores the thickness changes after cold pressing and assembly.

[0162] The battery cell is charged at 25°C at a constant current of 1 / 3C to 3.7V-4.4V, then charged at a constant voltage of 3.7V-4.4V to a current of 0.05C, and left for 5 minutes, and the thickness of the negative electrode film is h2;

[0163] The expansion rate of the negative electrode film layer is W=(h2-h1) / h1×100%, and W≤22%.

[0164] like Figure 7 As shown in the figure, along the stacking direction of the electrode sheets (the x direction of the coordinate axis), when the battery cell is in the initial state, the negative electrode film layer 12 has a first surface 12b and a second surface 12a that are arranged opposite to each other, and the distance between the first surface 12b and the second surface 12a is h1; when the battery cell is charged to a 100% SOC state at 25°C and a 1C rate, the negative electrode sheet 1 has a certain expansion. At this time, the negative electrode film layer 12 has a first surface 12b and a third surface 12a' that are arranged opposite to each other, and the distance between the first surface 12b and the third surface 12a' is h2. According to the calculation formula W=(h2-h1) / h1×100%, the expansion rate of the negative electrode film layer is calculated to be W≤22%.

[0165] When carbon nanotubes are not added to the negative electrode film layer of the present application, the expansion rate of the negative electrode film layer is greater than 22%. Compared with the existing method, the design method provided by the present application is conducive to reducing the expansion rate of the negative electrode plate.

[0166] In some embodiments, the compaction density of the negative electrode film is 1.55 g / cm 3 ~1.65g / cm 3 ;

[0167] The bonding force between the negative electrode film layer and the negative electrode current collector is 7N / m to 20N / m.

[0168] The cohesive force of the negative electrode film layer is 50 N / m to 200 N / m.

[0169] The compaction density in this application can be used to characterize the energy density of the material, and the compaction density of the negative electrode film layer is used to evaluate the compaction density of the entire negative electrode sheet. The compaction density of the negative electrode film layer = the surface density of the negative electrode film layer / the thickness of the negative electrode film layer. The thickness of the negative electrode film layer includes the distance between the two end faces of the negative electrode film layer along the thickness direction. The surface density of the negative electrode film layer = the weight of the single-sided positive electrode film layer / the area of ​​the single-sided positive electrode film layer. The weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of ​​the single-sided negative electrode film layer can be obtained by using the area calculation formula based on the shape of the film layer. This application lists the compaction density of the negative electrode film layer as 1.55g / cm in these embodiments. 3 ~1.65g / cm 3 The compaction density is not much different from that of the prior art, which indicates that the effect of adding carbon nanotubes on the compaction density of the negative electrode film layer is negligible.

[0170] The present application discloses in these examples that the compaction density of the negative electrode film layer is 1.55 g / cm 3 , 1.56g / cm 3 , 1.57g / cm 3 , 1.58g / cm 3 , 1.59g / cm 3 , 1.60g / cm 3 , 1.61g / cm 3 、1.62g / cm 3 、1.63g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 Any one of the above two ranges.

[0171] The bonding force between the negative electrode film layer and the negative electrode current collector of the present application refers to the magnitude of the binding force between the negative electrode film layer and the negative electrode current collector, and the magnitude of the bonding force can be measured by any conventional measurement method in the art, such as by using a tensile machine.

[0172] In these embodiments, the present application discloses that the bonding force between the negative electrode film layer and the above-mentioned negative electrode current collector is any one of 7N / m, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m, 18N / m, 19N / m, 20N / m or any one of the values ​​satisfying the above two ranges.

[0173] The cohesive force of the negative electrode film layer of the present application refers to the bonding force between the various material components in the negative electrode film layer. The magnitude of the cohesive force can be measured by any conventional measurement method in the art, such as by using a tensile machine.

[0174] The cohesive force of the negative electrode film layer in the present application is 50 N / m to 200 N / m, which indicates that the carbon nanotubes of the present application are well bound to the negative electrode active material.

[0175] In these embodiments, the present application discloses that the cohesive force of the negative electrode film layer is any one of 50N / m, 55N / m, 60N / m, 65N / m, 70N / m, 75N / m, 80N / m, 85N / m, 90N / m, 95N / m, 100N / m, 110N / m, 120N / m, 130N / m, 140N / m, 150N / m, 160N / m, 170N / m, 180N / m, 190N / m, and 200N / m, or any one of the values ​​satisfying the above two ranges.

[0176] In some embodiments, the negative electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.

[0177] In some embodiments, the negative electrode film layer further comprises any one or more of carbon black and graphene;

[0178] In some embodiments, the specific surface area of ​​the carbon black is ≥100 m 2 / g;

[0179] In some embodiments, the number of graphene layers is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm;

[0180] In some embodiments, the mass percentage of the carbon black and / or graphene in the positive electrode film layer is 0 to 2.5%.

[0181] The carbon nanotubes of the present application are used to bind the negative electrode active materials in the negative electrode film layer. At the same time, the carbon nanotubes themselves have very good conductivity and can also be used as a conductive agent for the negative electrode film layer. The conductive agent refers to a substance with conductivity. It plays the role of collecting microcurrents between the positive electrode active materials and between the positive electrode active materials and the positive electrode current collector, so as to reduce the contact resistance of the electrode and accelerate the movement rate of electrons.

[0182] The negative electrode film layer of the present application also includes other types of conductive agents, which together with carbon nanotubes form a conductive network, which is conducive to the fast charging of the battery at high rate use. The present application discloses in these embodiments that other types of conductive agents include any one or more of point-shaped conductive agents and planar conductive agents. Among them, the point-shaped conductive agent includes any one or more of graphite, carbon black, and carbon dots, and the planar conductive agent includes graphene.

[0183] The carbon black in the present application refers to one of the industrial products, which is mainly composed of carbon and contains small amounts of elements such as oxygen, hydrogen and sulfur.

[0184] The graphene of this application refers to sp 2 A one-atom-thick flat sheet of bonded carbon atoms, tightly packed in a honeycomb lattice.

[0185] The present application discloses in some embodiments that the conductive agent includes carbon black, graphene, and carbon nanotubes, wherein carbon black is mainly used as a point-like conductive agent, graphene is used as a sheet-like conductive agent, and carbon nanotubes are used as a one-dimensional tubular conductive agent, which is beneficial to forming a conductive network of a point-line-surface structure and thus improving the conductivity of the conductive agent. Therefore, the conductive agent of the present application can exert good conductivity at a relatively small usage amount, which is beneficial to exerting the fast charging performance of the battery under high-rate use.

[0186] The specific surface area determination method of the present application includes any conventional method in the art, such as referring to GB / T19587-2004, using nitrogen adsorption specific surface area analysis test method to test, and using BET (Brunauer Emmett Teller) method to calculate the specific surface area of ​​the porous carbon material. The test instrument can be TRISTAR II 3020 specific surface area and porosity analyzer from Micromeritics, USA.

[0187] The graphene of the present application has a sheet structure, and the sheet structure can be a single sheet or two or more sheets stacked together. The method for measuring the number of graphene layers includes any conventional method in the art, such as selecting the application area to be tested, using a projection electron microscope + electron diffraction method to determine the number of layers of the sample by changing the direction of the electron beam incident on the graphene and the change law of the intensity of the graphene diffraction spots under different electron beam incident angles.

[0188] The sheet diameter of each layer of the graphene sheet structure in the present application refers to the lateral size of the graphene sheet structure, wherein the average sheet diameter is the average of the sheet diameters of each layer, obtained by high-power electron microscope observation and measurement. The average measurement method here is any conventional method in the art.

[0189] The present application discloses in these examples that the specific surface area of ​​carbon black is 400 m 2 / g~3000m 2 / g.

[0190] The present application discloses in these examples that the specific surface area of ​​carbon black is 100 m 2 / g, 200m 2 / g、300m 2 / g, 400m2 / g、500m 2 / g, 600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g, 2400m 2 / g, 2600m 2 / g、2800m 2 / g、3000m 2 / g or any of the values ​​satisfying the above two ranges.

[0191] The present application discloses in these embodiments that the average flake diameter of each layer is any one of 2 μm, 2.5 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7.8 μm or any one of the values ​​within any two ranges above.

[0192] In these embodiments, the present application discloses that the mass percentage content of carbon black and / or graphene in the above-mentioned positive electrode film layer is any one of 0, 0.1%, 0.5%, 1%, 1.5%, 2.0%, 2.5% or any one of the ranges of any two of the above.

[0193] In some embodiments, the negative electrode film layer includes a binder;

[0194] The above-mentioned adhesive includes acryl-based copolymer;

[0195] The acryl copolymer comprises any one or more of a structural unit derived from an acrylic acid monomer, a structural unit derived from an acrylamide monomer, a structural unit derived from an acrylonitrile monomer, and a structural unit derived from an acrylate monomer;

[0196] The mass percentage content of the acryl-based copolymer in the negative electrode film layer is 1% to 3%.

[0197] The binder in the present application refers to a chemical compound, polymer or mixture that forms a colloidal solution or colloidal slurry in a dispersion medium.

[0198] The copolymer in this application refers to a polymerization reaction in which two or more monomers participate together, which is called copolymerization. The polymer formed contains two or more monomer units. This type of polymer is called a copolymer, also known as an interpolymer.

[0199] The propylene-based copolymers disclosed in these embodiments of the present application are mainly linear binders, which together with the carbon nanotubes facilitate better binding of the negative electrode active materials.

[0200] The present application discloses in these embodiments that the acrylic monomer comprises any one or more of acrylic acid, methacrylic acid, and ethacrylic acid.

[0201] The present application discloses in these embodiments that the acrylamide monomers include any one or more of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, diacetone acrylamide, N,N-dimethyl acrylamide, and N,N-methylenebisacrylamide.

[0202] The present application discloses in these embodiments that the acrylonitrile monomer includes any one or more of acrylonitrile, methacrylonitrile, and ethacrylonitrile.

[0203] The present application discloses in these embodiments that the acrylic acid ester monomers include any one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl methacrylate.

[0204] In some embodiments, the propylene copolymer includes methacrylic acid, N-hydroxymethyl acrylamide, acrylonitrile and n-butyl acrylate. The present application discloses in these embodiments that, in the propylene copolymer, based on the mass of the propylene copolymer, the mass percentage content of methacrylic acid is 20%, the mass percentage content of N-hydroxymethyl acrylamide is 35%, the mass percentage content of acrylonitrile is 15%, and the mass percentage content of n-butyl acrylate is 30%.

[0205] In some embodiments, the median particle size of the graphite is Dv50, which is 8 μm to 20 μm.

[0206] The Dv50 of the present application includes 50% of the volume of particles with a diameter larger than it and 50% of the volume of particles with a diameter smaller than it, which is also called the median diameter and is usually used to indicate the average particle size of particles. The present application selects to refer to the laser diffraction particle size analysis method in these embodiments, specifically refers to the standard GB / T19077-2016 to obtain the particle size distribution diagram, and then obtains it by calculation. The test instrument can be selected from Malvern MasterSize 3000.

[0207] In these examples, the present application discloses that the median particle size of the graphite satisfies the above-mentioned range value. On the one hand, the graphite is convenient to be bound and entangled by carbon nanotubes. On the other hand, the graphite with this median particle size has a certain expansion rate when used at a high rate. The design method provided in the present application is conducive to reducing the expansion degree of the graphite.

[0208] In these embodiments, the present application discloses that the median particle size Dv50 of the graphite is any one of 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, and 20μm, or any one of the values ​​satisfying any two of the above ranges.

[0209] In some embodiments, the graphite comprises a porous structure, and the pore volume of the graphite is 1.0 cm 3 / g~3.0cm 3 / g.

[0210] The present application discloses in some embodiments that graphite comprises a porous structure, wherein the porous structure comprises mesopores, micropores and macropores. The porous structure enhances the wettability of graphite to electrolyte, thus facilitating the use of graphite under high-rate fast charging conditions.

[0211] The pore volume in this application refers to the pore volume. The pore volume determination method of the graphite in this application includes any conventional method in the art, such as testing the pore volume of porous carbon materials according to GB / T 21650.2-2008. The testing instrument can be the TRISTAR II 3020 specific surface area and porosity analyzer of Micromeritics, USA.

[0212] The present application discloses in these examples that the pore volume of graphite is 1.0 cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g, 1.8cm 3 / g, 1.9cm 3 / g, 2.0cm 3 / g, 2.1cm 3 / g, 2.2cm 3 / g, 2.3cm 3 / g, 2.4cm 3 / g, 2.5cm 3 / g, 2.6cm 3 / g, 2.7cm 3 / g, 2.8cm 3 / g, 2.9cm 3 / g, 3.0cm 3 / g or any of the values ​​satisfying any two of the above ranges.

[0213] In some embodiments, the oil absorption value of the above graphite is 45cm 3 / 100g~65cm 3 / 100g.

[0214] The oil absorption value of this application refers to the volume (cm2) of dibutyl phthalate (DBP) absorbed by 100g of graphite under specified test conditions. 3 ) number. It is used to characterize the aggregation degree of graphite.

[0215] The measurement method of the oil absorption value of the present application includes conventional known methods in the art, specifically referring to the national standard GB / T3780.2-2003 "Determination of the absorption value of dibutyl phthalate in carbon black part 2" which stipulates method A (instrumental method), and the testing instrument is, for example, the oil absorption meter produced by Brabender of Germany.

[0216] The oil absorption value of the graphite in this application is 45cm 3 / 100g~65cm 3 / 100g, which is related to the porous structure of the above-mentioned graphite, which is beneficial to increase the liquid absorption capacity of the negative electrode film layer to the electrolyte and improve the wettability of the negative electrode plate to the electrolyte, which is beneficial to the use of graphite under high-rate fast charging conditions and reduces the expansion degree of the negative electrode plate of the battery under high-rate charging and discharging conditions.

[0217] [Negative electrode]

[0218] The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode film layer located on one side surface or both sides surface of the negative electrode current collector. Generally speaking, the negative electrode film layer is located on both sides surface of the negative electrode current collector, and the formation method includes coating or deposition. The present application will take both sides as an example in the following.

[0219] The present application discloses in some embodiments that the conductive agent, in addition to carbon nanotubes, includes one or more of point-shaped conductive agents, other linear conductive agents, and planar conductive agents, wherein the point-shaped conductive agent includes but is not limited to conductive carbon black (Super P or Super S), acetylene black, conductive graphite (KS-6 or KS-15 or SFG-6 or SFG-15), and one or more of Ketjen black, the linear conductive agent includes carbon nanofibers, and the planar conductive agent includes but is not limited to graphene.

[0220] The present application discloses in some embodiments that the negative electrode film layer may contain other binders and dispersants in addition to the above-mentioned propylene copolymer as a binder, and the binder includes but is not limited to polyvinyl alcohol, polyethylene glycol, sodium carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyacrylamide, sodium alginate, styrene-butadiene rubber (SBR), etc. The dispersant also includes any conventional type in the art, such as cellulose and its salts, specifically including but not limited to methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc. Among them, the sodium carboxymethyl cellulose as a binder and / or dispersant may be the same as or different from the sodium carboxymethyl cellulose in the carbon nanotube dispersion.

[0221] The present application discloses in some embodiments that the material of the negative electrode current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector. The present application also discloses in these embodiments that the metal foil includes copper foil, aluminum foil, stainless steel foil, iron foil, zinc foil, titanium foil, etc. The present application also discloses in these embodiments that the metal foam current collector includes copper foam, aluminum foam, zinc foam, etc. The present application also discloses in these embodiments that the metal mesh current collector includes copper mesh, aluminum mesh, etc. At the same time, the negative electrode current collector can also be a composite current collector formed by a composite of a metal foil and a metal foam, or a composite current collector formed by a composite of a metal foil and a metal mesh, or a composite current collector formed by a composite of a metal foil and a polymer base film, which is not particularly limited in the present application.

[0222] The method for forming the negative electrode film layer of the present application includes mixing the above-mentioned raw materials with a solvent (such as deionized water) in a certain mass ratio to form a negative electrode slurry, defoaming the negative electrode slurry, and then evenly coating the negative electrode slurry on both sides of the negative electrode collector; controlling the single-sided coating weight; drying, and compacting to a certain compaction density using a cold press to obtain a negative electrode sheet containing a negative electrode film layer.

[0223] [Method for preparing negative electrode sheet]

[0224] According to some embodiments of the present application, a method for preparing a battery cell is disclosed, comprising the following process:

[0225] Providing a carbon nanotube dispersion comprising carbon nanotubes, a first dispersant and a first solvent;

[0226] Preparing negative electrode slurry: dispersing the negative electrode active material, the carbon nanotube dispersion and the second dispersant in the second solvent, and mixing them to form negative electrode slurry;

[0227] Preparing a negative electrode sheet: coating a negative electrode slurry on at least one side of a negative electrode current collector to form a negative electrode film layer;

[0228] Prepare battery cells: Assemble the negative electrode sheet, positive electrode sheet and separator together.

[0229] In some embodiments, the first dispersant includes sodium carboxymethyl cellulose, and the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.7 and less than 1.0;

[0230] The above-mentioned second dispersant includes sodium carboxymethyl cellulose, and the substitution degree of the sodium carboxymethyl cellulose is 1.0 to 1.2. As mentioned above, the carbon nanotubes of the present application have the advantages of winding and binding the negative electrode active material and reducing the expansion degree of the negative electrode active material, but the dispersibility of the carbon nanotubes themselves is not good, especially the smaller the tube diameter and the longer the tube length, the worse the dispersibility of the carbon nanotubes, which makes it easy for the carbon nanotubes to agglomerate in the dispersion and thus affects the performance of their performance. In order to improve the agglomeration problem, the present application selects sodium carboxymethyl cellulose with a small substitution degree in the carbon nanotube dispersion to improve the dispersibility of the carbon nanotubes. In the process of preparing the negative electrode slurry, graphite is also easy to agglomerate, so it is also selected to add a second dispersant in the slurrying process.

[0231] The sodium carboxymethyl cellulose of the present application refers to a linear polymer derivative of cellulose containing multiple anhydroglucose units (β-linked pyranose glucose residues), each glucose unit has 3 hydroxyl groups, the hydrogen in the hydroxyl groups is replaced by carboxymethyl groups, and the average number of substituted hydroxyl groups per anhydroglucose unit is defined as the degree of substitution (DS).

[0232] The substitution degree of sodium carboxymethyl cellulose in the present application affects the rheology, dispersibility and stability of the dispersed material. The present application selects the substitution degree of sodium carboxymethyl cellulose in the carbon nanotube dispersion to be less than that in the negative electrode slurry for better dispersion of different substances at different stages.

[0233] The present application discloses in these embodiments that the degree of substitution of sodium carboxymethyl cellulose in the first dispersant is any one of 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, etc., or any one of the values ​​satisfying the above two ranges.

[0234] The present application discloses in these embodiments that the degree of substitution of sodium carboxymethyl cellulose in the second dispersant is any one of 1.0, 1.1, 1.2 or any one of the values ​​within the above two ranges.

[0235] In some embodiments, the carbon nanotube dispersion further comprises a surfactant, and the mass percentage content of the surfactant is 2% to 3%;

[0236] The above-mentioned surfactant includes any one or more of glutamic acid surfactant and glycine surfactant.

[0237] The glutamic acid surfactant of the present application refers to a compound whose anion contains glycine as a hydrophilic group and whose cation contains a C8-C20 alkyl group. Similarly, the glycine surfactant of the present application refers to a compound whose anion contains glycine as a hydrophilic group and whose cation contains a C8-C20 alkyl group.

[0238] The carbon nanotube dispersion of the present invention contains 2% to 3% by weight of a glutamic acid surfactant and / or a glycine surfactant, which is beneficial to further increase the dispersion of the carbon nanotubes and improve the solid content of the carbon nanotube dispersion.

[0239] In some embodiments, the solid content of the carbon nanotube dispersion is 0.6% to 1.5%.

[0240] The solid content of the present application refers to the mass percentage of solid matter in the carbon nanotube dispersion. The solid content can be determined by any conventional determination method in the art, for example, refer to DB13_T 5025.1-2019:

[0241] Weigh 2g of carbon nanotube dispersion sample into an empty weighing dish with constant mass, spread it evenly, and the mass before drying is m1. Place the weighing dish with the sample in an electric constant temperature air drying oven at 120℃±2℃ and dry it for 3h. After cooling, obtain the total mass of the weighing dish and the sample after drying, m20. Put it into an electric constant temperature air drying oven at 120℃±2℃ and dry it for 30min. Take it out and weigh m21. Repeat this operation until the difference between the last two weighings is no more than 0.0003g. When calculating, take the average value of the mass of the last two weighings as m2, then the solid content = m2 / m1*100%.

[0242] In these embodiments, the present application discloses that the solid content of the carbon nanotube dispersion is any one of 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any one of the values ​​satisfying any two of the above ranges.

[0243] In some embodiments, in the carbon nanotube dispersion, the mass ratio of the carbon nanotubes to the first dispersant is 100:(50-250).

[0244] The present application selects a first dispersant of a certain weight and a certain dosage to disperse the carbon nanotubes. The carbon nanotubes are not easy to agglomerate under the premise of having a certain tube length and have better dispersibility.

[0245] In these embodiments, the present application discloses that the mass ratio between the carbon nanotubes and the first dispersant is any one of 100:50, 100:60, 100:70, 100:80, 100:90, 100:100, 100:110, 100:120, 100:130, 100:140, 100:150, 100:160, 100:170, 100:180, 100:190, 100:200, 100:210, 100:220, 100:230, 100:240, 100:250 or any one of the values ​​satisfying the above ranges.

[0246] In some embodiments, the first solvent comprises nitrogen-methylpyrrolidone (NMP).

[0247] In some embodiments, the second solvent comprises deionized water.

[0248] [Positive electrode]

[0249] According to some embodiments of the present application, as described above, the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises a positive electrode active material.

[0250] The structure and composition of the positive electrode film layer of the present application are as described above, and will not be elaborated herein.

[0251] In some embodiments of the present application, the compaction density of the positive electrode film layer is 2.5 g / cm 3 ~3.4g / cm 3 .

[0252] The compacted density of the positive electrode film layer of the present application can be used to characterize the energy density of the material, the compacted density of the positive electrode film layer = the surface density of the positive electrode film layer / the thickness of the positive electrode film layer, the thickness of the positive electrode film layer includes the distance between the two end faces of the positive electrode film layer along the thickness direction, the surface density of the positive electrode film layer = the weight of the single-sided positive electrode film layer / the area of ​​the single-sided positive electrode film layer, wherein the weight of the single-sided positive electrode film layer can be obtained by weighing, and the area of ​​the single-sided positive electrode film layer can be obtained by using the area calculation formula according to the shape of the film layer.

[0253] In some embodiments of the present application, the positive electrode active material of the present application includes but is not limited to one or a combination of two or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and olivine structure lithium phosphate; wherein the structural formula of the olivine structure lithium phosphate is: LiFe 1-x- y Mn x M y PO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M includes one or more combinations of transition metal elements or non-transition metal elements other than Fe and Mn, and M preferably includes one or more combinations of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr. The present application specifically includes but is not limited to LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM111), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 CO 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 CO 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 CO 0.15 Al 0.05 One or more of O2, LiFePO4 (LFP) and LiMnPO4.

[0254] According to some embodiments of the present application, the positive electrode film layer also includes a conductive agent, a binder, etc. The conductive agent includes but is not limited to one or more combinations of graphite, superconducting carbon, carbon black (such as acetylene black, Ketjen black, Super P, etc.), carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder includes but is not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylate resin, styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, carboxymethyl chitosan, etc. One or more combinations. The positive electrode current collector in the present application can be a metal foil or a composite current collector, wherein the metal foil can be an aluminum foil, and the composite current collector can include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming metal materials such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0255] The method for forming the positive electrode film layer of the present application comprises mixing the above raw materials with a solvent (such as N-methylpyrrolidone) in a certain mass ratio to form a positive electrode slurry, and evenly coating the positive electrode slurry on both sides of the positive electrode current collector; controlling a certain single-sided coating weight; and after drying, using a cold press to compact to a certain compaction density (2.5g / cm 3 ~3.4g / cm 3 ), that is, a positive electrode sheet including a positive electrode film layer is obtained.

[0256] [Isolator]

[0257] Some embodiments of the present application disclose an isolating element. The present application has no particular limitation on the type of isolating element, and any known porous isolating element with good chemical stability and mechanical stability can be selected.

[0258] In some embodiments, the separator includes a base material layer and a coating disposed on the surface of the base material layer; the base material of the base material layer includes one or more of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide and polyamide; the coating includes a ceramic coating and / or a polymer coating. The base material layer has a good permeability to lithium ions, which is beneficial to the migration of lithium ions; the surface of the base material layer is provided with a coating, and the coating can further improve the mechanical properties of the separator. Optionally, the ceramic particles in the ceramic coating include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2 and BaSO4. Optionally, the polymer material of the polymer coating includes one or more of polyethylene (PE), polypropylene (PP), polyphenylene terephthalamide (PPTA), polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI) and polyamide (PA). The polymer coating and the base material layer can be made of the same or different materials, and the thickness of the polymer coating and the base material layer can be different. Optionally, the thickness of the polymer coating is less than the thickness of the base material layer.

[0259] In other embodiments, the material of the spacer can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The spacer can be a single-layer film or a multi-layer composite film, without particular limitation. When the spacer is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0260] [Electrolyte]

[0261] In some embodiments of the present application, an electrolyte is disclosed. The electrolyte of the present application may be in liquid, solid, or gel state. Among them, the solid state is a solid electrolyte, the liquid state is a liquid electrolyte, and the gel state is a gel electrolyte. The lithium-ion battery of the present application uses a liquid electrolyte, that is, an electrolyte. The electrolyte contains an electrolyte salt and an organic solvent. Among them, the types of electrolyte salts include any conventional types in the art, for example, including but not limited to inorganic metal salts, such as RClO4, RAsF6, RPF6, RBF4, RSbF6, RSO3F, RN(FSO2)2, etc.; fluorine-containing organic metal salts, such as RCF3SO3, RN(FSO2)(CF3SO2), RN(CF3SO2)2, RN(C2F5SO2)2, cyclic 1,3-hexafluoropropane disulfonyl imide lithium, cyclic 1,2-tetrafluoroethane disulfonyl imide lithium, RN(CF3SO2)(C4F9S O2), RC(CF3SO2)3, RPF4(CF3)2, RPF4(C2F5)2, RPF4(CF3SO2)2, RPF4(C2F5SO2)2, RBF2(CF3)2, RBF2(C2F5)2, RBF2(CF3SO2)2, RBF2(C2F5SO2)2, etc.; and metal salts containing dicarboxylic acid complexes, such as lithium bis(oxalato)borate, lithium difluorooxalatoborate, lithium tris(oxalato)phosphate, lithium difluorobis(oxalato)phosphate, lithium tetrafluoro(oxalato)phosphate, etc. The metal and R here both contain lithium ions.

[0262] According to some embodiments of the present application, the concentration of the electrolyte salt in the electrolyte is 0.1mol / L to 4mol / L. The present application discloses in these embodiments that the concentration of the electrolyte salt is 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L, 2.2mol / L, 2.5mol / L, 2.8mol / L, 3mol / L, 3.2mol / L, 3.5mol / L, 3.8mol / L, 4mol / L, or any one of the values ​​satisfying the above range.

[0263] As described above, the organic solvent includes any one or more of carboxylic acid ester compounds, carbonate compounds, and ether compounds. Among them, the carboxylic acid ester compounds include one or more of ethyl acetate (EA), methyl acetate (MA), ethyl propionate (EP), propyl acetate (PA), methyl propionate (MP), methyl butyrate (MB), ethyl butyrate (EB), and 1,4-butyrolactone (GBL); the carbonate compounds include one or more of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), and fluoroethylene carbonate (FEC). The ether compounds include at least one of tetrahydrofuran, dimethyltetrahydrofuran, tetrahydropyran, dimethyltetrahydropyran, 1,2-dimethoxyethane, dipropylene glycol dimethyl ether, or dimethyl phthalate. The organic solvent of the present application further comprises one or two of nitrile solvents and sulfone solvents, wherein the nitrile solvent comprises one or more of acetonitrile (AN), glutaronitrile (GLN) and adiponitrile (ADN). The sulfone solvent comprises at least one or a combination of two of sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0264] According to some embodiments of the present application, the electrolyte further comprises a film-forming stabilizer, which comprises a positive electrode film-forming stabilizer and a negative electrode film-forming stabilizer, wherein the positive electrode film-forming stabilizer comprises carbonate additives and / or sulfate additives, and the carbonate additives include one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), vinyl ethylene carbonate (VEC) and dioctyl carbonate (CC). Sulfate additives include cyclic sulfonate additives and / or alkyl sulfate additives; further, cyclic sulfonate additives include one or more of 1,3-propane sultone (PS), propylene sultone (PES), and 3-fluoro-1,3-propane sultone (FPS); alkyl sulfate additives include one or more of vinyl sulfate (DTD), diethyl sulfate (DES) and dimethyl sulfate (DMS). The negative electrode film-forming stabilizer includes one or more of boron lithium salts, phosphorus-containing lithium salts and sulfur-containing lithium salts; boron-containing lithium salts include one or more of lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB) and lithium bis(fluorooxalatoborate) (LiDFOB); phosphorus-containing lithium salts include one or more of lithium difluorophosphate (LiPO2F2), lithium fluorophosphate (Li2PO3F) and lithium phosphate (Li3PO4). Sulfur-containing lithium salts include one or more of lithium fluorosulfonate (LiFSO3), lithium sulfate (Li2SO4) and lithium sulfamate (LiSO3NH2).

[0265] The battery cell of the present application will be described in detail below in conjunction with specific embodiments.

[0266] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0267] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0268] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.

[0269] Experimental materials:

[0270] 1. Carbon nanotube dispersion: commercially available;

[0271] 2. Propylene copolymer: (comprising methacrylic acid, N-hydroxymethyl acrylamide, acrylonitrile and n-butyl acrylate, based on the mass of the propenyl copolymer, the mass percentage content of methacrylic acid is 20%, the mass percentage content of N-hydroxymethyl acrylamide is 35%, the mass percentage content of acrylonitrile is 15%, the mass percentage content of n-butyl acrylate is 30%, and the weight average molecular weight is 500,000), commercially available;

[0272] 3. SBR: commercially available;

[0273] 4. Graphite: commercially available;

[0274] 5. Lithium nickel cobalt manganese oxide: commercially available;

[0275] 6. Carbon black: commercially available;

[0276] 7. Graphene: Commercially available.

[0277] The composition of the carbon nanotube dispersion and the parameters and properties of the carbon nanotubes in this application are shown in Table 1-1.

[0278] Table 1-1 Composition of carbon nanotube dispersion

[0279]

[0280] The substitution degree of sodium carboxymethyl cellulose in the carbon nanotube dispersion shown in Table 1-1 is 0.85, and the weight average molecular weight is 200,000.

[0281] The surfactant shown in Table 1-1 is a glycine-based surfactant, the anion of which is glycine and the cation of which is octadecyl.

[0282] In addition to the carbon nanotube dispersion shown in Table 1-1 above, the present application also uses carbon nanotubes with an average tube length of 10 μm. The carbon nanotube dispersion contains carbon nanotubes, hydrogenated nitrile rubber (HNBR, with a weight average molecular weight of 216,000, acrylonitrile content of 38% by mass in the hydrogenated nitrile rubber, and a degree of hydrogenation of 98.0%) and solvent nitrogen methyl pyrrolidone (NMP), and the solid content of the carbon nanotube dispersion is 1%; named 1-6.

[0283] The present application also provides several negative electrode active materials, the parameters and performances of the negative electrode active materials are shown in Table 1-2.

[0284] Table 1-2 Properties of graphite

[0285] Serial number Median particle size / μm <![CDATA[Pore volume / cm 3 / g]]> <![CDATA[Oil absorption value / cm 3 / 100 g]]> Change multiple of loose volume before and after expansion 2-1 10.5 2.97 65 253 2-2 18.9 1.46 45 116 2-3 15.3 1.05 10 85

[0286] The method for determining the change multiple of the loose volume of graphite before and after expansion in Table 1-2 refers to the loose density, such as GB / T1479.1-2011.

[0287] The types of raw materials illustrated in the above Tables 1-1 and 1-2 of the present application are only for illustrating the inventive concept of the present application. In fact, other types that meet the protection scope of the present application are also within the protection scope of the present application.

[0288] Example 1

[0289] A battery cell is provided. The battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked in sequence, and also comprises an electrolyte.

[0290] The specific preparation process is as follows:

[0291] The preparation of the negative electrode sheet comprises the following steps:

[0292] Providing a carbon nanotube dispersion: the carbon nanotube dispersion of sequence number 1-1 as shown in Table 1-1;

[0293] Preparation of negative electrode slurry: Disperse the carbon nanotube dispersion and the graphite of sequence number 2-1 shown in Table 1-2, the binder SBR and the dispersant sodium carboxymethyl cellulose (substitution degree 1.0, weight average molecular weight 400,000) in deionized water to form a negative electrode slurry;

[0294] Preparation of negative electrode sheet: Apply the negative electrode slurry to at least one side of the negative electrode current collector, dry it, and then use a cold press to compact it to a certain compaction density to prepare a negative electrode sheet. The proportions of each component in the negative electrode film layer of the negative electrode sheet are shown in Table 1-3 below. Place the negative electrode film layer sample on the sample stage of the scanning electron microscope, put it into the electron microscope chamber, evacuate it, turn on the electron beam, and set appropriate parameters for characterization: the parameters for observing the morphology are 10kV, the working distance is 4.4mm, and the electron microscope image of the negative electrode film layer is as follows Figure 8 Indicate, combine Figure 8 It can be seen that the carbon nanotubes are attached to and entangled on the surface of the negative electrode active material.

[0295] Preparation of positive electrode sheet:

[0296] Take LiNi 0.8 CO 0.1 Mn 0.1 O2, conductive carbon black, and PVDF were mixed in a ratio of 96.5:2.5:1, and N-methylpyrrolidone solvent was added and stirred to form a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and heated and dried. Specifically, a multi-section oven was used, and the temperature settings were 120℃ / 100℃ / 90℃, and then a cold press was used for compaction to obtain a positive electrode sheet with a compaction density of 3.2g / cm 3 The positive electrode.

[0297] Prepare electrolyte:

[0298] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, diethyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain a solvent, and lithium salt lithium hexafluorophosphate is added to the solvent to form an electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L.

[0299] Isolators available:

[0300] A porous polyethylene (PE) film with a thickness of 13 μm was used as the separator.

[0301] Preparation of battery cells:

[0302] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the stacked bare cells are assembled accordingly; the stacked bare cells are placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a battery cell is obtained.

[0303] Example 1-1

[0304] A method for preparing a battery cell is provided. The method is different from Example 1 in that, during the preparation of the negative electrode slurry, the amount of carbon nanotube dispersion added is adjusted so that the content of carbon nanotubes in the positive electrode film layer is different. The specific addition amounts are shown in Tables 1-3. Other aspects of this embodiment remain the same as Example 1.

[0305] Comparative Example 1

[0306] A method for preparing a battery monomer is provided. The method is different from Example 1 in that no carbon nanotube dispersion is used. In the process of preparing the negative electrode slurry, graphite and carbon black (with a specific surface area of ​​650 m 2 / g), binder SBR and dispersant sodium carboxymethyl cellulose (substitution degree is 1.0, weight average molecular weight is 400,000) are dispersed in deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of the negative electrode current collector to form a negative electrode film layer.

[0307] Comparative Example 2

[0308] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that, in the process of preparing the negative electrode slurry, the carbon nanotube dispersions numbered 1-6 are used, and the rest are the same as in Example 1, and the average tube length of the carbon nanotubes in the negative electrode film layer is 35.1 μm.

[0309] Comparative Example 3

[0310] A method for preparing a battery cell is provided. The method is different from Example 1 in that, during the preparation of the negative electrode slurry, no dispersant is added to the carbon nanotube dispersion, and the average tube length of the carbon nanotubes in the final negative electrode film layer is 5.7 μm.

[0311] The compositions and contents of the negative electrode film layers of the above embodiments and comparative examples are shown in Tables 1-3 below:

[0312] Table 1-3 Composition and content of negative electrode film layer

[0313]

[0314]

[0315] In Tables 1-3 of the present application, the first dispersant and the second dispersant belong to the same general category, but have different degrees of substitution and weight average molecular weights. The degree of substitution of the first dispersant (sodium carboxymethyl cellulose, CMC) is less than 1.0, and the degree of substitution of the second dispersant (sodium carboxymethyl cellulose, CMC) is 1.0. The total mass percentage of the first dispersant and the second dispersant in the positive electrode film layer is 1.5%. The negative electrode film layer of Comparative Example 1 uses carbon black as a conductive agent, and the specific surface area of ​​the carbon black is 650m2 / g, and the mass percentage content of carbon black in the negative electrode film layer is 2%.

[0316] The performance of the negative electrode sheet was tested according to the following determination method:

[0317] (1) Determination of compaction density of negative electrode film:

[0318] Take the negative electrode sheet samples prepared in the above embodiments and comparative examples, and use a cryo-focused ion beam (FIB) to finely slice the negative electrode sheet layer by layer at different thickness positions, and separate different layers of samples at different thickness positions;

[0319] First, a scanning electron microscope is used to take pictures to obtain the thickness H of each negative electrode film layer;

[0320] The mass of the negative electrode film layer is weighed as M0, and the test area is S0; then the surface density of the negative electrode film layer is D=M0 / S0;

[0321] Then the compaction density of the negative electrode film layer = the surface density D of the negative electrode film layer / the thickness H of the negative electrode film layer.

[0322] Similarly, the present application obtains multiple negative electrode film layer samples at different positions along the length direction of the negative electrode film for the first negative electrode film layer and the second negative electrode film layer, and the compaction density value of each negative electrode film layer sample is measured according to the above-mentioned measurement method, and then the average value of each compaction density value is taken: (compacted density 1+compacted density 2+compacted density 3…+compacted density n) / n, which is the compaction density value of the first negative electrode film layer or the second negative electrode film layer.

[0323] (2) Test of the bonding strength of the negative electrode sheet:

[0324] The equipment used is: Zhongzhi Testing Tensile Machine (model LXG2-LLCS-0009) for testing; the specific test process is as follows:

[0325] ① Use a blade to cut a negative electrode sample with a width of 30mm and a length of (90mm to 150mm), and stick the double-sided tape on the steel plate with a width of 20mm and a length of (90mm to 150mm).

[0326] ② Paste the negative electrode sample in step ① onto the double-sided tape, wherein the exposed outer side of the negative electrode sample is used as the test surface, and roll the test surface three times along the same direction with a roller with a width of 20 mm;

[0327] ③ Turn on the power of the tensile testing machine, fix the end of the steel plate without the negative electrode sheet with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base, fold the negative electrode sheet pasted on the steel plate upwards, and fix it with the upper clamp.

[0328] ④ Start pre-tensioning, pre-tensioning about 5mm, then "clear" the "force" and "displacement" parameters. After the two parameters are reset to zero, click the start button to start the test, and then record the test results. Perform three sets of tests in parallel according to the above steps, calculate the average value N1, and the final bonding force = N1×50.

[0329] (3) Cohesion test of negative electrode:

[0330] The method for obtaining the negative electrode film layer is as described above.

[0331] The equipment used for the test is Instron 336; the specific test process is as follows:

[0332] Cut the negative electrode film layer into a sample with a length of 100 mm and a width of 10 mm. Take a stainless steel plate with a width of 25 mm and paste the sample on the stainless steel plate with a 3M double-sided tape (width 11 mm), where the current collector is bonded to the double-sided tape. Use a 2000g roller to roll back and forth on the sample surface three times (300 mm / min). Then paste a 10 mm wide and 50 μm thick tape (model NITTO.NO5000NS) on the surface of the negative electrode film layer, and use a 2000g roller to roll back and forth on its surface three times (300 mm / min). Bend the tape 180 degrees, manually peel off the tape and the negative electrode film layer by 25mm, fix the sample on the Instron 336 tensile tester, keep the peeling surface consistent with the tester force line (i.e., perform 180° peeling), pre-pull 10mm at a peeling speed of 100mm / min, restore the displacement of the tensile tester, and finally peel continuously at 300mm / min to obtain the cohesion curve. Take the average value of the stable section as the peeling force F0, and calculate the cohesion F1 of the tested electrode by the following formula: F1 = F0 / width of the sample to be tested, and the unit of measurement of F1 is N / m.

[0333] The performance parameters shown in the following table are obtained.

[0334] Table 1-4 Performance list of negative electrode film layer

[0335] Adhesion force / N / m Cohesion / N / m <![CDATA[Compaction density / g / cm 3 > Example 1 14.4 138 1.65 Example 1-1 10.1 102 1.65 Comparative Example 1 5.7 35 1.65 Comparative Example 2 8.3 82 1.65 Comparative Example 3 6.2 37 1.65

[0336] From Tables 1-4, it can be seen that the carbon nanotubes designed in the present application are beneficial to increasing the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer, and within a certain range, the higher the content of carbon nanotubes, the more obvious the increase in the cohesive force between the components in the negative electrode film layer.

[0337] Example 2-1

[0338] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that the carbon nanotube dispersion numbered 1-1 in Table 1-1 is replaced with the carbon nanotube dispersion numbered 1-2, and the rest is the same as in Example 1.

[0339] Example 2-2

[0340] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that the carbon nanotube dispersion liquid numbered 1-1 in Table 1-1 is replaced with the carbon nanotube dispersion liquid numbered 1-3, and the rest is the same as in Example 1.

[0341] Example 2-3

[0342] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that the carbon nanotube dispersion numbered 1-1 in Table 1-1 is replaced with the carbon nanotube dispersion numbered 1-4, and the rest is the same as in Example 1.

[0343] Embodiment 2-4

[0344] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that the carbon nanotube dispersion numbered 1-1 in Table 1-1 is replaced with the carbon nanotube dispersion numbered 1-5, and the rest is the same as in Example 1.

[0345] Embodiment 2-5

[0346] A method for preparing a battery cell is provided. The method differs from that of Example 1 in that the carbon nanotube dispersion numbered 1-1 in Table 1-1 is replaced by the carbon nanotube dispersion numbered 1-2 (the carbon nanotube content in the negative electrode film layer is 0.3%) and the carbon nanotube dispersion numbered 1-3 (the carbon nanotube content in the negative electrode film layer is 0.2%).

[0347] The compositions and contents of the negative electrode films of Examples 2-1 to 2-5 are shown in Table 2-1 below:

[0348] Table 2-1 Composition and content of negative electrode film layer

[0349]

[0350]

[0351] According to the above test method, the performance parameters of the negative electrode plate are obtained as shown in Table 2-2 below.

[0352] Table 2-2 Performance list of negative electrode film layer

[0353] Adhesion force / N / m Cohesion / N / m <![CDATA[Compaction density / g / cm 3 > Example 1 14.4 138 1.65 Example 2-1 13.6 125 1.65 Example 2-2 12.8 110 1.65 Example 2-3 11.1 99 1.65 Embodiment 2-4 9.7 91 1.65 Embodiment 2-5 13.2 118 1.65

[0354] It can be seen from Table 2-2 that the longer the average tube length of the carbon nanotubes and the smaller the average tube diameter, the more obvious the improvement in the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer. And it can be seen from Example 1, Example 2-1, Example 2-2 and Example 2-5 that the use of a certain amount of carbon nanotubes with a long tube length and a small average tube diameter in combination with carbon nanotubes with a short tube length and a large average tube diameter can also play a role in significantly enhancing the cohesive force between the components in the negative electrode film layer.

[0355] Example 3-1

[0356] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that, during the preparation of the negative electrode slurry, the graphite numbered 2-1 shown in Table 1-2 is replaced with 2-2, and the rest is the same as in Example 1.

[0357] Example 3-2

[0358] A method for preparing a battery cell is provided. The method is different from that in Example 1 in that, during the preparation of the negative electrode slurry, the graphite numbered 2-1 shown in Table 1-2 is replaced with 2-3, and the rest is the same as in Example 1.

[0359] The compositions and contents in the above examples are shown in Table 3-1 below:

[0360] Table 3-1 Composition and content of negative electrode film layer

[0361]

[0362] According to the above test method, the performance parameters of the negative electrode plate are obtained as shown in Table 3-2 below.

[0363] Table 3-2 Performance list of negative electrode film layer

[0364] Adhesion force / N / m Cohesion / N / m <![CDATA[Compaction density / g / cm 3 > Example 1 14.4 138 1.65 Example 3-1 12.9 114 1.65 Example 3-2 11.0 103 1.65

[0365] From Table 3-2, it can be seen that the parameters such as the particle size and pore volume of graphite also affect the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer. Generally speaking, the larger the pore volume of graphite, the greater its own expansibility. After the carbon nanotubes are added for winding and binding in the present application, the cohesive force between the components in the negative electrode film layer is also improved more significantly.

[0366] Example 4-1

[0367] A method for preparing a battery monomer is provided. The method is different from that of Example 1 in that, in the process of preparing the negative electrode slurry, the carbon nanotube dispersion of sequence number 1-1 shown in Table 1-1 and the graphite and carbon black (specific surface area of ​​650 m 2 / g), graphene (7 layers on average, with an average sheet diameter of 6.8 μm for each layer), binder SBR and dispersant sodium carboxymethyl cellulose (degree of substitution of 1.0) were dispersed in deionized water to form a negative electrode slurry; the rest was the same as in Example 1. The composition and content of the negative electrode film layer are shown in Table 4-1.

[0368] Table 4-1 Composition and content of negative electrode film layer

[0369]

[0370]

[0371] According to the above test method, the performance parameters of the negative electrode plate are obtained as shown in Table 4-2 below.

[0372] Table 4-2 Performance list of negative electrode film layer

[0373] Adhesion force / N / m Cohesion / N / m <![CDATA[Compaction density / g / cm 3 > Example 1 14.4 138 1.65 Example 4-1 14.2 135 1.65

[0374] Combined with Table 4-2, it can be seen that other types of conductive agents in the negative electrode film layer except carbon nanotubes have little effect on the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer.

[0375] Example 5-1

[0376] A method for preparing a battery monomer is provided. The method is different from that in Example 1 in that, during the preparation of the negative electrode slurry, the binder SBR is replaced with the above-mentioned polypropylene-based polymer (weight average molecular weight is 500,000), and the rest remains the same as in Example 1.

[0377] Among them, the components and contents of the negative electrode film layer are shown in Table 5-1.

[0378] Table 5-1 Composition and content of negative electrode film layer

[0379]

[0380]

[0381] According to the above test method, the performance parameters of the negative electrode plate are obtained as shown in Table 5-2 below.

[0382] Table 5-2 Performance list of negative electrode film layer

[0383] Adhesion force / N / m Cohesion / N / m <![CDATA[Compaction density / g / cm 3 > Example 1 14.4 138 1.65 Example 5-1 15.6 142 1.65

[0384] Combined with Table 5-2, it can be seen that in the negative electrode film layer, the use of carbon nanotubes with a certain tube length and a polypropylene-based binder further increases the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer to a certain extent.

[0385] (4) Test method for pole piece expansion rate:

[0386] In the above process of preparing the negative electrode sheet, after cold pressing, the thickness of the negative electrode film layer is h1 (thickness after cold pressing);

[0387] At 25°C, fully charge the battery (charged to 3.8V at 1 / 3C constant current, then charged to 0.05C at 3.8V constant voltage, and left for 5 minutes), disassemble the battery and take out the anode electrode, use a micrometer to test the thickness of 20 points on the outer, middle and inner circles of the electrode, take the average value to get h2, the electrode expansion rate = (h2-h1) / h1×100%.

[0388] (5) 1000 cycles of battery cell expansion force:

[0389] The battery cell is fixed in the first and second steel pieces of the three-piece steel fixture, and the pressure sensor is placed in the second and third steel pieces. The bolts are tightened, and the preload force is set to 2000N. The battery cell is subjected to a cycle test: at 25°C, the battery is charged to 3.8V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage of 3.8V, left for 5 minutes, and then discharged to 2.0V at 1 / 3C, which is recorded as 1 cycle. According to this cycle test method, 1000 cycles are performed, and the pressure sensor monitors and records the maximum expansion force of each cycle.

[0390] (6) Number of cycles corresponding to a battery capacity retention rate of 80%:

[0391] At 25°C, charge the battery to 3.8V at 1 / 3C constant current, then charge at 3.8V constant voltage to a current of 0.05C, leave for 5 minutes, and then discharge to 2.0V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps and record the discharge capacity Cn of the battery after the nth cycle. The battery capacity retention rate after each cycle is Pn = Cn / C0*100%. In this test process, the number of cycles corresponding to Pn = 80% is n.

[0392] Table 6 Battery performance

[0393]

[0394]

[0395] It can be seen from Example 1 and Comparative Example 1 and Comparative Example 2 in Table 6 that the negative electrode film layer contains graphite and carbon nanotubes, and the average tube length of the carbon nanotubes is greater than or equal to 40 μm, which is beneficial to increase the bonding force between the negative electrode film layer and the negative electrode current collector and the cohesive force between the components in the negative electrode film layer, thereby reducing the expansion of the negative electrode plate and ultimately improving the cycle life of the battery.

[0396] It can be seen from Example 1 and Example 1-1 in Table 6 that by using the carbon nanotubes designed in the present application and controlling the content within a certain range, as the mass percentage of the carbon nanotubes in the negative electrode film layer increases, the expansion of the negative electrode plate is better suppressed and the cycle life of the battery is also better.

[0397] In combination with Example 1 and Example 5-1, it can be seen that the use of carbon nanotubes with a certain tube length designed in the present application in combination with a polypropylene-based binder is beneficial to further inhibit the expansion of the negative electrode plate and improve the cycle life of the battery.

[0398] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A battery cell, characterized in that: Including positive electrode sheet and negative electrode sheet; The negative electrode plate comprises a negative electrode current collector and a negative electrode film layer located on at least one side surface of the negative electrode current collector; The negative electrode film layer comprises a negative electrode active material and carbon nanotubes, and the average tube length of the carbon nanotubes is greater than or equal to 40 μm; The negative electrode active material includes graphite.

2. The battery cell according to claim 1, characterized in that: The average tube length of the carbon nanotubes is 60 μm to 500 μm.

3. The battery cell according to any one of claims 1 to 2, characterized in that: The average diameter of the carbon nanotubes is 0.8 nm to 20 nm.

4. The battery cell according to any one of claims 1 to 3, characterized in that: The tensile strength of the carbon nanotubes is 30 GPa to 55 GPa; and / or, The elastic modulus of the carbon nanotubes is 0.5TPa-0.9TPa.

5. The battery cell according to any one of claims 1 to 4, characterized in that: The carbon nanotubes include single-walled carbon nanotubes, and based on the mass of the negative electrode film layer, the mass percentage content of the single-walled carbon nanotubes is C1, 0.3%≤C1≤1.5%; The average tube diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm.

6. The battery cell according to any one of claims 1 to 5, characterized in that: The carbon nanotubes include multi-walled carbon nanotubes, and based on the mass of the negative electrode film layer, the mass percentage content of the multi-walled carbon nanotubes is C2, 0.5%≤C2≤1.5%; The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm.

7. The battery cell according to any one of claims 1 to 6, characterized in that: The carbon nanotubes include single-walled carbon nanotubes and multi-walled carbon nanotubes. The average diameter of the single-walled carbon nanotubes is 0.8 nm to 2 nm; The average diameter of the multi-walled carbon nanotubes is greater than 2 nm and less than or equal to 20 nm; Based on the mass of the negative electrode film layer, the mass percentage content of the single-walled carbon nanotube is C1, and the mass percentage content of the multi-walled carbon nanotube is C2, satisfying: (C2×3 / 5+C1)≥0.3%; 0.3%≤C1≤1.5%; 0.5%≤C2≤1.5%.

8. The battery cell according to any one of claims 1 to 7, characterized in that: The compaction density of the negative electrode film layer is 1.55 g / cm 3 ~1.65g / cm 3 ; The bonding force between the negative electrode film layer and the negative electrode current collector is 7N / m to 20N / m; The cohesive force of the negative electrode film layer is 50 N / m to 200 N / m.

9. The battery cell according to any one of claims 1 to 8, characterized in that: The negative electrode film layer further comprises any one or more of a point-shaped conductive agent and a surface-shaped conductive agent.

10. The battery cell according to any one of claims 1 to 9, characterized in that: The negative electrode film layer further comprises any one or more of carbon black and graphene.

11. The battery cell according to claim 10, characterized in that: The specific surface area of ​​the carbon black is ≥100m 2 / g; and / or; The number of graphene layers is 1 to 10, and the average sheet diameter of each layer is 2 μm to 8 μm.

12. The battery cell according to any one of claims 10 to 11, characterized in that: The mass percentage of the carbon black and / or graphene in the positive electrode film layer is greater than zero and less than or equal to 2.5%.

13. The battery cell according to any one of claims 1 to 12, characterized in that: The negative electrode film layer includes a binder; The binder includes a propylene-based copolymer; The acryl-based copolymer includes any one or more of a structural unit derived from an acrylic acid monomer, a structural unit derived from an acrylamide monomer, a structural unit derived from an acrylonitrile monomer, and a structural unit derived from an acrylate monomer.

14. The battery cell according to claim 13, characterized in that: The mass percentage content of the propylene-based copolymer in the negative electrode film layer is 1% to 3%.

15. The battery cell according to any one of claims 1 to 14, characterized in that: The median particle size of the graphite: Dv50 is 8 μm to 20 μm.

16. The battery cell according to any one of claims 1 to 15, characterized in that: The graphite comprises a porous structure, and the pore volume of the graphite is 1.0 cm 3 / g~3.0cm 3 / g.

17. The battery cell according to any one of claims 1 to 16, characterized in that: The oil absorption value of the graphite is 45cm 3 / 100g~65cm 3 / 100g.

18. A method for preparing a battery monomer according to claim 1, characterized in that: The process includes the following: Providing a carbon nanotube dispersion comprising carbon nanotubes, a first dispersant and a first solvent; Preparing negative electrode slurry: dispersing the negative electrode active material, the carbon nanotube dispersion and the second dispersant in the second solvent, and mixing them to form negative electrode slurry; Preparing a negative electrode sheet: coating a negative electrode slurry on at least one side of a negative electrode current collector to form a negative electrode film layer; Prepare battery cells: Assemble the negative electrode sheet, positive electrode sheet and separator together.

19. The preparation method according to claim 18, characterized in that: The first dispersant includes sodium carboxymethyl cellulose, and the degree of substitution of the sodium carboxymethyl cellulose is greater than or equal to 0.7 and less than 1.0; The second dispersant includes sodium carboxymethyl cellulose, and the substitution degree of the sodium carboxymethyl cellulose is 1.0-1.

2.

20. The preparation method according to any one of claims 18 to 19, characterized in that: In the carbon nanotube dispersion, the mass ratio between the carbon nanotube and the first dispersant is 100:(50-250); and / or; The solid content of the carbon nanotube dispersion is 0.6% to 1.5%.

21. The preparation method according to any one of claims 18 to 20, characterized in that: The carbon nanotube dispersion further includes a surfactant; In the carbon nanotube dispersion, the mass percentage content of the surfactant is 2% to 5%; The surfactant includes any one or more of a glutamic acid surfactant and a glycine surfactant.

22. A battery device, characterized in that: A battery cell comprising the battery cell according to any one of claims 1 to 17 or a battery cell prepared by the preparation method according to any one of claims 18 to 21.

23. An electrical device, characterized in that: A battery device comprising the battery device of claim 22.

Citation Information

Cited By

  • High-rate negative pole piece and preparation method thereof, sodium ion battery and electric equipment

    CN120674429A